Occurrence of Leptospira Species from Rodents, Soil and Water from an Oil Palm Plantation in Northern Sarawak - Lesley, Maurice Bilung; Chai, Fung Pui; Ahmad Syatir, Tahar; Kasing, Apun; Lela, Su’ut; Yee, Ling Chong; Jayasilan, Mohd-Azlan (Academic Journals Inc., 2018)
Leptospirosis is a death-causing disease caused by corkscrew-shaped bacteria, Leptospira especially in tropical countries. Current study was aimed to detect pathogenic, intermediate and saprophytic Leptospira species using polymerase chain reaction (PCR) assay from an oil palm plantation in Borneo, specifically in Miri, Malaysia. Materials and Methods: A total of 63 samples from rodents (n = 3), water (n = 30) and soil (n = 30) were isolated from an oil palm estate in Northern Sarawak, Borneo. All samples were inoculated into modified semisolid Ellinghausen-McCullough-Johnson-Harris (EMJH) broth with 5-fluorouracil and incubated for a month. Polymerase chain reaction (PCR) was performed using primer targeting lipL32 (423 bp) for pathogenic, 16S rRNA (331 bp) for intermediate and rrs (240 bp) for saprophytic species.